الحماية القانونية للمعطيات الشخصية للمستهلك الالكتروني - جعلاب مسعودة (جامعة المسيلة, 2021)
تعد المعطيات الشخصية جوهر حماية حق الشخص في الخصوصية , هذه الأخيرة تعد من المفاهيم المرنة التي تتغير من وقت لآخر و من مكان لآخر حسب التطورات التكنولوجية الحاصلة لذا فان التشريع الجزائري كرس لحماية قانونية في بعض القوانين ذات الصلة , غير أن هذه القوانين لا توفر الحماية اللازمة و الكافية للشخص أو الفرد صاحب المعطيات المعالجة , مما دفع بالمشرع القيام بخطوة جريئة فسن قانون خاص بحماية المعطيات الشخصية يتمثل في القانون 18_07 المتعلق بحماية الأشخاص في مجال معالجة المعطيات ذات الطابع الشخصي , غير أن الواقع العملي لا يزال بعيدا نتيجة عدم صدور المرسوم التنفيذي الخاص بتشكيلة و مهام السلطة الوطنية المسؤولة عن حماية المعطيات ذات الطابع الشخصي . Abstract The protection of personal data is the essence of protecting the personal right of privacy. The latter is one of the most flexible concepts thatchange from time to time and from one place to another according to the technological developments taking place. Therefore, the Algerian legislation has devoted legal protection in some relevant laws, but these laws do not provide the necessary and sufficient protection for the person or the individual who is the possessor of the processed data. This prompted the legislator to take a forward step by enacting a special law for the protection of personal data represented in the law 18_07 which is related to the protection of natural persons in the field of personal data processing. However, practical reality is still remote as a result of the failure to issue the executive decree on the composition and the protection of personal data.